Epidemiological profile of leprosy reactions in a referral center in Campinas (SP), Brazil, 2010-2015 - Letícia Ambrosano; Marcel Alex Soares dos Santos; Elaine Cristina Faria Abrahão Machado; Elisangela Samartin Pegas (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Leprosy patients can present reactions during the course of the disease. There are no official data on these reactions in Brazil. We aimed to describe the epidemiological characteristics of patients with such reactions, analyzing information from patient records at a referral center in Campinas (SP), from 2010 to 2015.